2016
DOI: 10.1002/qre.2103
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches in Monitoring Multivariate Categorical Processes based on Contingency Tables in Phase II

Abstract: In some statistical process control (SPC) applications, quality of a process or product is characterized by contingency table. Contingency tables describe the relation between two or more categorical quality characteristics. In this paper, two new control charts based on the WALD and Stuart score test statistics are designed for monitoring of contingency table‐based processes in Phase‐II. The performances of the proposed control charts are compared with the generalized linear test (GLT) control chart proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For multivariate numerical variables, the 2 statistic can be calculated based on the mean vector and the covariance matrix of the variables. On the other hand, for multivariate categorical data, a contingency table is the most efficient tool with which to study the relationships of the categorical variables by presenting the count of the combinations of different levels of variables (Kamranrad 2017). However, for a dataset including both numerical and categorical variables, existing literature details few methods with which to deal with them simultaneously.…”
Section: A Mixture Of Numerical and Categorical Datamentioning
confidence: 99%
“…For multivariate numerical variables, the 2 statistic can be calculated based on the mean vector and the covariance matrix of the variables. On the other hand, for multivariate categorical data, a contingency table is the most efficient tool with which to study the relationships of the categorical variables by presenting the count of the combinations of different levels of variables (Kamranrad 2017). However, for a dataset including both numerical and categorical variables, existing literature details few methods with which to deal with them simultaneously.…”
Section: A Mixture Of Numerical and Categorical Datamentioning
confidence: 99%
“…The multivariate ordinal processes include more than one ordered factor, for which multivariate categorical control charts based on the OLLM are used. Statistical Process Monitoring (SPM) uses contingency tables to monitor multivariate category processes simultaneously [2]. As well as, OLLM used to demonstrate the relevance between ordinal variables and correlative observations in an ordinal contingency table (OCT) cell.…”
Section: Introductionmentioning
confidence: 99%
“…In phase II, they showed that the proposed control chart was robust to detect different shifts. Afterwards, the GLT statistic proposed to monitor multivariate processes in phase-II by Kamranrad et al [2]. As well as, GLT is mixed with an EWMA statistic to enhance performance in small and medium shifts.…”
Section: Introductionmentioning
confidence: 99%
“…There are also control charts developed for multivariate categorical data. One may refer to Patel (1973), Marcucci (1985), Lu et al (1998), Li et al (2012;2014a), and Kamranrad et al (2017). As for monitoring multivariate Poisson counts, recent works include Chiu and Kuo (2008), He et al (2014) and Wang et al (2017).…”
Section: Introductionmentioning
confidence: 99%